Equine neorickettsiosis: A global perspective of the natural habitat of the bacteria and clinical disease - Luis G. Arroyo; Alexandre S. Borges; John D. Baird; Brian D. Perry; Yasuko Rikihisa; Stephen E. Greiman (Veterinary Microbiology, 2026)

CRISPR Epigenome Editing of IL1R1 Expression of Neurons that Innervate the Temporomandibular Joint or Knee Causes Reduced Sensitization to Osteoarthritic Environment - Joshua D. Stover; Robby D. Bowles; Yenisel Cruz-Almeida; Robert M. Caudle; Kyle D. Allen; Armen Akopian; Benjamin Arenkiel; Basak Ayaz; Yangjin Bae; Bruna Balbino de Paula; Anita Bandrowski; Mario Danilo Boada; et al. (Annals of Biomedical Engineering, 2026)

Evaluating top‐down, bottom‐up, and environmental drivers of pelagic food web dynamics along an estuarine gradient - Tanya L. Rogers; Samuel M. Bashevkin; Christina E. Burdi; Denise D. Colombano; Peter N. Dudley; Brian Mahardja; Lara Mitchell; Sarah Perry; Parsa Saffarinia (Ecology, 2024)
Identification of the key biotic and abiotic drivers within food webs is important for understanding species abundance changes in ecosystems, particularly across ecotones where there may be strong variation in interaction strengths. Using structural equation models (SEMs) and four decades of integrated data from the San Francisco Estuary, we investigated the relative effects of top‐down, bottom‐up, and environmental drivers on multiple trophic levels of the pelagic food web along an estuarine salinity gradient and at both annual and monthly temporal resolutions. We found that interactions varied across the estuarine gradient and that the detectability of different interactions depended on timescale. For example, for zooplankton and estuarine fishes, bottom‐up effects appeared to be stronger in the freshwater upstream regions, while top‐down effects were stronger in the brackish downstream regions. Some relationships (e.g., bottom‐up effects of phytoplankton on zooplankton) were seen primarily at annual timescales, whereas others (e.g., temperature effects) were only observed at monthly timescales. We also found that the net effect of environmental drivers was similar to or greater than bottom‐up and top‐down effects for all food web components. These findings can help identify which trophic levels or environmental factors could be targeted by management actions to have the greatest impact on estuarine forage fishes and the spatial and temporal scale at which responses might be observed. More broadly, this study highlights how environmental gradients can structure community interactions and how long‐term data sets can be leveraged to generate insights across multiple scales.

Gelatinous and soft-bodied zooplankton in the Northeast Pacific Ocean: Phosphorus content and potential resilience to phosphorus limitation - Florian Lüskow; Moira D. Galbraith; Brian P. V. Hunt; R. Ian Perry; Maarten Boersma; Evgeny A. Pakhomov (Hydrobiologia, 2022)

The scope and severity of white‐nose syndrome on hibernating bats in North America - Tina L. Cheng; Jonathan D. Reichard; Jeremy T. H. Coleman; Theodore J. Weller; Wayne E. Thogmartin; Brian E. Reichert; Alyssa B. Bennett; Hugh G. Broders; Joshua Campbell; Katherine Etchison; Daniel J. Feller; Richard Geboy; et al. (Conservation Biology, 2021)
Assessing the scope and severity of threats is necessary for evaluating impacts on populations to inform conservation planning. Quantitative threat assessment often requires monitoring programs that provide reliable data over relevant spatial and temporal scales, yet such programs can be difficult to justify until there is an apparent stressor. Leveraging efforts of wildlife management agencies to record winter counts of hibernating bats, we collated data for 5 species from over 200 sites across 27 U.S. states and 2 Canadian provinces from 1995 to 2018 to determine the impact of white‐nose syndrome (WNS), a deadly disease of hibernating bats. We estimated declines of winter counts of bat colonies at sites where the invasive fungus that causes WNS ( Pseudogymnoascus destructans ) had been detected to assess the threat impact of WNS. Three species undergoing species status assessment by the U.S. Fish and Wildlife Service ( Myotis septentrionalis , Myotis lucifugus , and Perimyotis subflavus ) declined by more than 90%, which warrants classifying the severity of the WNS threat as extreme based on criteria used by NatureServe. The scope of the WNS threat as defined by NatureServe criteria was large (36% of Myotis lucifugus range) to pervasive (79% of Myotis septentrionalis range) for these species. Declines for 2 other species ( Myotis sodalis and Eptesicus fuscus ) were less severe but still qualified as moderate to serious based on NatureServe criteria. Data‐sharing across jurisdictions provided a comprehensive evaluation of scope and severity of the threat of WNS and indicated regional differences that can inform response efforts at international, national, and state or provincial jurisdictions. We assessed the threat impact of an emerging infectious disease by uniting monitoring efforts across jurisdictional boundaries and demonstrated the importance of coordinated monitoring programs, such as the North American Bat Monitoring Program (NABat), for data‐driven conservation assessments and planning.

Primates and Cameras - Brian D. Gerber; Perry J. Williams; Larissa L. Bailey (International Journal of Primatology, 2014)

Establishing a reference group for distal 18q-: clinical description and molecular basis - Jannine D. Cody; Minire Hasi; Bridgette Soileau; Patricia Heard; Erika Carter; Courtney Sebold; Louise O’Donnell; Brian Perry; Robert F. Stratton; Daniel E. Hale (Human Genetics, 2014)

The safety of studies with intravenous Δ9-tetrahydrocannabinol in humans, with case histories - Michelle Carbuto; R. Andrew Sewell; Ashley Williams; Kim Forselius-Bielen; Gabriel Braley; Jacqueline Elander; Brian Pittman; Ashley Schnakenberg; Savita Bhakta; Edward Perry; Mohini Ranganathan; Deepak Cyril D’Souza (Psychopharmacology, 2012)

Polyamines are required for the expression of key Hms proteins important for Yersinia pestis biofilm formation - Brian W. Wortham; Marcos A. Oliveira; Jacqueline D. Fetherston; Robert D. Perry (Environmental Microbiology, 2010)
Summary We previously showed that mutations in the genes encoding the two main biosynthetic enzymes responsible for polyamine production, arginine decarboxylase (SpeA) and ornithine decarboxylase (SpeC) cause a loss of biofilm formation in Yersinia pestis . In Y. pestis the development of a biofilm is dependent on 6 Hms (hemin storage) proteins (HmsH, F, R, S, T and P) grouped into 3 operons; hmsHFRS , hmsT and hmsP . In this article we show that polyamines are necessary to maintain the levels of key Hms proteins. In the absence of polyamines there is an ∼93%, ∼43% and ∼90% reduction in protein levels of HmsR, HmsS and HmsT respectively. Overexpression of hmsR and hmsT from plasmids alone can restore biofilm formation to a SpeA ‐ SpeC ‐ mutant. Addition of exogenous putrescine also restores normal levels of HmsR, HmsS, HmsT and biofilm production. Analyses using transcriptional reporters and quantitative RT‐PCR indicate that the initiation of transcription and mRNA stability are not reduced by polyamine deficiency. Instead, translational reporters indicate that polyamines function at least in part by modulating the translation of HmsR and HmsT. Although construction of a consensus Shine–Dalgarno sequence upstream of hmsT modestly reduced the stimulation of translation by putrescine, additional mechanisms likely contribute to the polyamine‐dependent expression of HmsT. Finally, we have shown that polyamines play a role in bubonic plague.

The effects of cannabinoids on serum cortisol and prolactin in humans - Mohini Ranganathan; Gabriel Braley; Brian Pittman; Thomas Cooper; Edward Perry; John Krystal; Deepak Cyril D’Souza (Psychopharmacology, 2009)

Preliminary evidence of cannabinoid effects on brain-derived neurotrophic factor (BDNF) levels in humans - Deepak Cyril D’Souza; Brian Pittman; Edward Perry; Arthur Simen (Psychopharmacology, 2009)

Effects of haloperidol on the behavioral, subjective, cognitive, motor, and neuroendocrine effects of Δ-9-tetrahydrocannabinol in humans - Deepak Cyril D’Souza; Gabriel Braley; Rebecca Blaise; Michael Vendetti; Stephen Oliver; Brian Pittman; Mohini Ranganathan; Savita Bhakta; Zoran Zimolo; Thomas Cooper; Edward Perry (Psychopharmacology, 2008)

Effects of graded levels of exercise on ipsilateral and contralateral post-exercise resting rectus femoris mechanomyography - William P. S. McKay; Perry Jacobson; Philip D. Chilibeck; Brian L. F. Daku (European Journal of Applied Physiology, 2006)

Population-Based Evaluation of the Ehrlichia Ruminantium MAP 1B Indirect ELISA - Trevor F. Peter; Christopher J. O'Callaghan; Graham F. Medley; Brian D. Perry; Shalt M. Semu; Suman M. Mahan (Experimental and Applied Acarology, 2001)

DNA Isolation and AFLP™ Genetic Fingerprinting of shape Theobroma cacao (L.) - Matthew D. Perry; Michael R. Davey; J. Brian Power; Kenneth C. Lowe; H. Frances J. Bligh; Paul S. Roach; Chris Jones (Plant Molecular Biology Reporter, 1998)

Effects of Land‐Use and Tsetse Fly Control on Bird Species Richness in Southwestern Ethiopia - Cathleen J. Wilson; Robin S. Reid; Nancy L. Stanton; Brian D. Perry (Conservation Biology, 1997)
Successful control of tsetse (Glossina spp.)‐transmitted trypanosomiasis in the Ghibe Valley, Ethiopia, appears to have accelerated conversion of wooded grassland into cropland. Land conversion, in turn, may have fragmented wildlife habitat. Our objective was to assess the influence of the expansion of agricultural land‐use, brought about by tsetse control, on ecological properties by using bird species richness and composition as indicators of environmental impacts. We sampled bird species richness and composition (using Timed‐Species counts) and habitat structure (using field sampling and remote sensing) in four land cover/land‐use types in areas subjected to tsetse fly control and adjacent areas without control. At the height of the growing season bird species numbers and vegetative complexity were greater in the small‐holder, oxen‐plowed fields and riparian woodlands than in wooded grasslands or in large‐holder, tractor‐plowed fields. Species composition was highly dissimilar (40–70% dissimilarity) comparing among land‐use types, with many species found only in a single type. This implies that trypanosomiasis control that results in land conversion from wooded grasslands to small‐holder farming in this region may have no adverse impacts on bird species numbers but will alter composition. These results also suggest that moderate land‐use by humans (e.g., small‐holder field mosaics) increases habitat heterogeneity and bird species richness relative to high levels of use (e.g., tractor‐plowed fields). Tsetse control may be indirectly maintaining species richness in the valley by encouraging the differential spread of these small‐scale, heterogeneous farms in place of large‐scale, homogeneous farms. Nevertheless, if the extent of small‐holder farms significantly exceeds that of present levels, negative impacts on bird species richness and large shifts in species composition may occur.